Percepção de aprendizagens de alunos de cursos de engenharia sobre o Método de Newton-Raphson pelo uso de mapas conceituais - Alves, Paulo Cesar (2016)
This developed search has the objective of analyse the conceptuals maps as a reflection instrument related to the understandment of a method to calculate the aproaches of real roots for high degree students. The chosen method is known as Newton-Raphson Method (NRM), that is normally part of the Numerical Calculus or Quantitative Methods and Computer subjects, that use the Derivated contant studied for first-year-engeneer students mainly in the subject of Differencial and Integral Cauculus. What was investigated was: how conceptuals maps can be used to understand as engeneer students can understan the NRM and its relation to Differencial and Integral Cauculus? Was used a quantitative aproache to this search that is situated at the educational field of Mathmatics. The theorical part is fundamented to the Learning Significative Theory of David Ausubel, using the Conceptual Maping of Joseph Novak. This search was developed with engeneer high degree students of a private institutuion, it was used the CmapTools software to the elaboration of digital conceptuals maps for the students. The final results were analysed with the objective of: firstly, try to realize students learnings about the NRM, obtained when students studied the subject of Numerical Calculus or Quantitative Methods and Computer. After we tryed to identify possible learnings that had an assimilation obliteradora. For this, the participants developed two conceptual maps using the CmapTools, the first map was elaborated with no influence of the searcher and the second was elaborated after a presentation of the method. The first conceptual digital maps elaborated for the participants revealed they understood how to elaborate a conceptual map using the CmapTools program, although they elaborated simple maps, with little relation to the used concepts. They also could present a NRM description in a logic way, revealing the students still remember some concepts envolved NRM and they also could present some relation that envolve these concepts. In relation to the second digital conceptual map, the students demostrated concepts that were not presented at the first digital conceptual map, some were elaborated with different structures and presented new terms of logic and coherence. In some maps is possible to realize the students remembered concepts studied in NRM and tryed to related to their maps by propositions. However, in some maps it is possible to detect the students only tryed to insert some NRM elements presented by the teacher. We also could realize that some studied concepts related to NRM seem to be interacting in the cognitive structure with previous knowledge, and with the NRM presentation, we concluded that some of these concepts seem to be present in a assimilation obliteradora